Staphylococcus aureus Fibronectin-Binding Protein A Mediates Cell-Cell Adhesion through Low-Affinity Homophilic Bonds. - GEOGHEGAN, JOAN; FOSTER, TIMOTHY (My University, 2015)
Staphylococcus aureus is an important opportunistic pathogen which is a leading cause of biofilm-associated infections on indwelling medical devices. The cell surface-located fibronectin-binding protein A (FnBPA) plays an important role in the accumulation phase of biofilm formation by methicillin-resistant S. aureus (MRSA), but the underlying molecular interactions are not yet established. Here, we use single-cell and single-molecule atomic force microscopy to unravel the mechanism by which FnBPA mediates intercellular adhesion. We show that FnBPA is responsible for specific cell-cell interactions that involve the FnBPA A domain and cause microscale cell aggregation. We demonstrate that the strength of FnBPA-mediated adhesion originates from multiple low-affinity homophilic interactions between FnBPA A domains on neighboring cells. Low-affinity binding by means of FnBPA may be important for biofilm dynamics. These results provide a molecular basis for the ability of FnBPA to promote cell accumulation during S. aureus biofilm formation. We speculate that homophilic interactions may represent a generic strategy among staphylococcal cell surface proteins for guiding intercellular adhesion. As biofilm formation by MRSA strains depends on proteins rather than polysaccharides, our approach offers exciting prospects for the design of drugs or vaccines to inhibit protein-dependent intercellular interactions in MRSA biofilms. IMPORTANCE Staphylococcus aureus is a human pathogen that forms biofilms on indwelling medical devices, such as central venous catheters and prosthetic joints. This leads to biofilm infections that are difficult to treat with antibiotics because many cells within the biofilm matrix are dormant. The fibronectin-binding proteins (FnBPs) FnBPA and FnBPB promote biofilm formation by clinically relevant methicillin-resistant S. aureus (MRSA) strains, but the molecular mechanisms involved remain poorly understood. We used atomic force microscopy techniques to demonstrate that FnBPA mediates cell-cell adhesion via multiple, low-affinity homophilic bonds between FnBPA A domains on adjacent cells. Therefore, FnBP-mediated homophilic interactions represent an interesting target to prevent MRSA biofilms. We propose that such homophilic mechanisms may be widespread among staphylococcal cell surface proteins, providing a means to guide intercellular adhesion and biofilm accumulation.
PUBLISHED
Keywords: Staphylococcus aureus; Staphylococcus aureus; Genes & Society; Immunology, Inflammation & Infection; Next Generation Medical Devices; BACTERIAL BIOFILMS; BIOFILM; METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS; Molecular Biology; STAPHYLOCOCCUS AUREUS